Advantages of using a nanomodified mesh with an antiseptic in the surgical treatment of abdominal hernia - Ruslan Lutkovskyi (Journal of Education, Health and Sport, 2022)
Surgical treatment of open operations for abdominal hernias (AH) using classic techniques of allogeneoplasty (sublay, onlay) is often accompanied by an increase in intra-abdominal pressure (IBP) and a decrease in the volume of the abdominal cavity, which in the postoperative period leads to abdominal compartment syndrome (ACS) In 2 ,4 - 3.6% of cases and mortality in 1.2 - 3.4% of observations. This requires a special method of closing a large defect of the abdominal wall, which would not increase ICP. The use of improved techniques contributes to the creation of the optimal volume of the abdominal cavity and improves the results of treatment, in particular, the frequency of ACS decreases. But it should be noted that the use of combined operations with a classic polypropylene mesh leads to a high frequency of complications from the postoperative wound, such as seroma (30.8 - 60.4%), suppuration of the postoperative wound (4.8 - 6.4%), ligature fistula (1.2 - 3.0%), meshoma (0.06 - 1.60%).